2018
DOI: 10.1186/s13104-018-3480-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of glycemic control in type 2 diabetes in the Eastern Sudan

Abstract: ObjectivesA cross-sectional study was conducted in Gadarif, eastern Sudan to assess glycaemic control among adult patients with type 2 diabetes in eastern Sudan. Poor glycaemic control was defined as HbA1c level of ≥ 7.0%. Questionnaire was used to gathered sociodemographic and clinical characteristics.ResultsA total of 339 patients (69.9% were women) were enrolled in the study. The mean age of the participants was 54.8 (12.8) years. Approximately more than two-thirds (n = 243, 71.7%) of the participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 24 publications
10
38
1
Order By: Relevance
“…The reported proportions are comparable to those reported in similar studies (cross-sectional in nature) from several countries in SSA-80% in Ethiopia [20], 73.52% in Uganda [14], 69.5% in Kenya [21], and 71.9% in Sudan [22]. In general, and the use of disparate HbA1c cut-offs notwithstanding, these values are patently inferior to those reported in some developed countries: 38% in USA [23] and 43.4% in Korea [24].…”
Section: Discussionsupporting
confidence: 86%
“…The reported proportions are comparable to those reported in similar studies (cross-sectional in nature) from several countries in SSA-80% in Ethiopia [20], 73.52% in Uganda [14], 69.5% in Kenya [21], and 71.9% in Sudan [22]. In general, and the use of disparate HbA1c cut-offs notwithstanding, these values are patently inferior to those reported in some developed countries: 38% in USA [23] and 43.4% in Korea [24].…”
Section: Discussionsupporting
confidence: 86%
“…Only 15% of 213 participants were fully adherent to their medications constituting a lower percentage than those (27). Another factor for poor adherence to medication is the fact that 62.4% of participants couldn't name the antidiabetic medications they were using.…”
Section: Discussionmentioning
confidence: 99%
“…This poor diabetes control can be attributed in part to poor diabetes medication adherence. A recent study in Eastern Sudan showed that 72% of type 2 diabetes have poor diabetes control ( 27 ). Another factor for poor adherence to medication is the fact that 62.4% of participants couldn’t name the antidiabetic medications they were using.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have confirmed the relationship between glycemic control and lipid profiles in patients with T2D, the results are quite inconsistent [ 9 , 10 , 11 ]. Khan HA et al reported that the level of HbA1c was positively correlated with TG, TC, and LDL-C, but negatively correlated with HDL-C [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Khan HA et al reported that the level of HbA1c was positively correlated with TG, TC, and LDL-C, but negatively correlated with HDL-C [ 10 ]. However, a cross-sectional study in Eastern Sudan showed that poor glycemic control was not associated with TG but was associated with high TC levels [ 11 ]. Furthermore, some studies showed that HbA1c was associated with TG and TC, rather than LDL-C and HDL-C [ 12 ].…”
Section: Introductionmentioning
confidence: 99%